Silicon Micro‐ and Nanofabrication for Medicine. Issue 5 (15th April 2013) - Fine, Daniel; Grattoni, Alessandro; Goodall, Randy; Bansal, Shyam S.; Chiappini, Ciro; Hosali, Sharath; van de Ven, Anne L.; Srinivasan, Srimeenkashi; Liu, Xuewu; Godin, Biana; Brousseau, Louis; Yazdi, Iman K.; et al.
Abstract This manuscript constitutes a review of several innovative biomedical technologies fabricated using the precision and accuracy of silicon micro‐ and nanofabrication. The technologies to be reviewed are subcutaneous nanochannel drug delivery implants for the continuous tunable zero‐order release of therapeutics, multi‐stage logic embedded vectors for the targeted systemic distribution of both therapeutic and imaging contrast agents, silicon and porous silicon nanowires for investigating cellular interactions and processes as well as for molecular and drug delivery applications, porous silicon (pSi) as inclusions into biocomposites for tissue engineering, especially as it applies to bone repair and regrowth, and porous silica chips for proteomic profiling. In the case of the biocomposites, the specifically designed pSi inclusions not only add to the structural robustness, but can also promote tissue and bone regrowth, fight infection, and reduce pain by releasing stimulating factors and other therapeutic agents stored within their porous network. The common material thread throughout all of these constructs, silicon and its associated dielectrics (silicon dioxide, silicon nitride, etc.), can be precisely and accurately machined using the same scalable micro‐ and nanofabrication protocols that are ubiquitous within the semiconductor industry. These techniques lend themselves to the high throughput production of exquisitely defined and monodispersed nanoscale features that should eliminate architectural randomness as a source of experimental variation thereby potentially leading to more rapid clinical translation.